An Innovative Approach to Primary Education: Teaching Text Comprehension Through Neuro-Pedagogical Strategies - Sotivoldiyeva Sarvinoz Khahramon Qizi (Indonesian Journal Publisher, 2025)
This article presents the results of a scientific study aimed at enhancing primary school students’ reading and text comprehension skills through the application of neuro-pedagogical strategies. The research was conducted using control and experimental groups, where the effectiveness of traditional methods and neuro-pedagogical approaches was compared. The implementation of strategies such as semantic analysis, visual mapping, and clustering in the experimental group significantly improved students’ reading speed, comprehension ability, and motivation. The study emphasizes the activation of cognitive processes and the harmonization of left and right brain hemispheres to improve information retention and understanding. Statistical analysis confirmed the effectiveness of these innovative methods, and the results provide a strong foundation for reforming literacy instruction in Uzbekistan's primary education system. The article concludes with recommendations for wider implementation and future integration with international educational practices